History of Ethics in Dialogue: Lévinas and Haidt on the Foundations of Morality - Pieszak, Eryk Józef (Sensus Historiae, 2025)
This article aims to assess the contemporary validity of Emmanuel Levinas’s ethical philosophy in the context of Jonathan Haidt’s empirical research in moral psychology. A comparative analysis is undertaken, aligning Levinas’s phenomenological ethics with Haidt’s theory of moral intuitionism. Levinas, through the concept of the Other, posits a primordial ethical imperative of responsibility that emerges in the face-to-face encounter with another human being. Haidt, by contrast, conceptualizes morality as a product of evolved emotional and socio-cognitive mechanisms, emphasizing the intuitive foundations of moral judgment. The analysis suggests that while Haidt’s moral foundations theory reveals the culturally and socially constructed variability of moral reasoning, Levinas’s framework - though situated within philosophical discourse - offers a potentially universal ethical paradigm grounded in intersubjective obligation.